Pendampingan Penggunaan Media Kartu Untuk Meningkatkan Kemampuan Menulis Huruf Hijaiyah Bersambung Di Desa Wonorejo-Kencong - Nafsah, Nor Holis bin; Himmah, Riris Faiqotul (INAIFAS Press, 2024)
Knowing and learning about hijaiyah letters is very important, especially for Muslims. However, due to the low level of education in our country in the past, the majority of people, especially housewives, were actually Hija'iyyah illiterate. Therefore, the use of card media to improve the ability to write continuous Hijaiyah letters in Wonorejo-Kencong Village is very relevant in this service process. It is hoped that by implementing this card media, the assisted objects will be able to read the Continuous Hijaiyah Letters accurately and correctly. The research method used in this research is a qualitative method. This research concludes that the use of card media can improve the ability to write continuous hijaiyah letters on assisted objects in Wonorejo-Kencong Village.